Babao Dan inhibits the migration and invasion of gastric cancer cells by suppressing epithelial–mesenchymal transition through the TGF-β/Smad pathway. Issue 6 (June 2020) - Liu, Jianxin; Chen, Yongan; Cao, Zhiyun; Guan, Bin; Peng, Jun; Chen, Youqin; Zhan, Zhixue; Sferra, Thomas Joseph; Sankararaman, Senthilkumar; Lin, Jiumao
Objective: To investigate the anti-metastatic effects of Babao Dan (BBD) on gastric cancer (GC) cells (AGS and MGC80-3) and explore the underlying molecular mechanisms by which it inhibits epithelial–mesenchymal transition (EMT). Methods: AGS and MGC80-3 cells were treated with BBD. In addition, cells were treated with the EMT inducer transforming growth factor-β1 (TGF-β1). Cell viability was determined using the MTT assay, and the live cell ratio was calculated via cell counting. Cell invasion and migration were evaluated using the Transwell assay. Western blotting was performed to measure the protein expression of EMT biomarkers and related genes. Results: BBD inhibited the viability, migration, and invasion of AGS and MGC80-3 cells, but it did not reduce the live cell ratio. Furthermore, BBD inhibited the expression of N-cadherin, vimentin, zinc finger E-box binding homeobox (ZEB)1, ZEB2, Twist1, matrix metalloproteinase (MMP)2, MMP9, TGF-β1, and p-Smad2/3, whereas E-cadherin expression was increased in AGS and MGC80-3 cells to different degrees. Using a GC cell model of EMT induced by TGF-β1, we proved that BBD inhibited p-Smad2/3 and N-cadherin expression, cell migration, and cell invasion. Conclusion: BBD suppressed cell migration and invasion by inhibiting TGF-β–induced EMT and inactivating TGF-β/Smad signaling in GC cells.